Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa Melalui Model Pembelajaran Course Riview Horay SDN Sumbermulyo 02 Pati - Pasuri Pasuri (Al Hikmah: Journal of Education, 2020)
This study aims to describe the learning process using the Course Riview Horay learning model, to find out whether through the Course Riview Horay learning model the activities of class V SD Negeri Sumbermulyo 02, and to find out whether the Course Riview Horay learning model can improve learning outcomes Theme 7 Subtema 1 Learning 2 grade V SD Negeri Sumbermulyo 02 for the 2019/2020 academic year. This type of research, namely Classroom Action Research, was carried out in 2 cycles with class V research subjects. Based on the analysis of the results of observations for 2 cycles of action and discussion, it can be concluded that: 1) By using the Course Review Horay Model, the learning outcomes Theme 7 Sub-theme 1 Learning 2 experienced improvement in both quantity and quality, 2) This learning technique is in accordance with the learning method desired by students, 3) This learning model is in accordance with the group learning atmosphere to stimulate student creativity and activity. The results showed that the learning outcomes increased significantly from the initial cycle of 43% (3 students) to complete and the average grade of the next 64 to 71% (5 students) to complete and the average of class 74 in the first cycle and increase to 100% ( 7 students) completed and an average of 89 in cycle II. The results also showed that individual learning activity increased significantly. Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran menggunakan model pembelajaran Course Riview Horay, mengetahui apakah melalui model pembelajaran Course Riview Horay terhadap aktivitas siswa kelas V SD Negeri Sumbermulyo 02, dan untuk mengetahui apakah melalui model pembelajaran Course Riview Horay dapat meningkatkan hasil belajar Tema 7 Subtema 1 Pembelajaran 2 siswa kelas V SD Negeri Sumbermulyo 02 tahun pelajaran 2019/2020. Jenis penelitian ini yaitu Penelitian Tindakan Kelas dilaksanakan dalam 2 siklus dengan subyek penelitian kelas V. Berdasarkan analisis hasil observasi selama 2 siklus tindakan dan pembahasan, dapat disimpulkan bahwa: 1) Dengan penggunaan Model Course Review Horay, hasil pembelajaran Tema 7 Subtema 1 Pembelajaran 2 mengalami peningkatan baik secara kuantitas maupun kualitas, 2) Teknik pembelajaran ini sesuai dengan cara pembelajaran yang diinginkan oleh siswa, 3) Model pembelajaran ini sesuai suasana pembelajaran berkelompok untuk merangsang daya kreatifitas dan keaktivan siswa. Hasil penelitian menunjukkan bahwa hasil belajar meningkatan secara signifikan dari siklus awal 43% (3 siswa) tuntas dan nilai rata-rata kelas 64 selanjutnya menjadi 71% (5 siswa) tuntas dan rata-rata kelas 74 pada siklus I dan meningkat menjadi 100% (7 siswa) tuntas dan rata-rata 89 pada siklus II. Hasil penelitian juga menunjukkan bahwa keaktivan belajar individu meningkat secara signifikan.